Implementasi Buku Ajar Kimia SMA Berbasis Masalah terhadap Peningkatan Kemampuan Berpikir Kritis Siswa pada Materi Laju Reaksi - Mayzul Fiahzia; Ratu Evina Dibyantini (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the effect of implementing problem-based high school chemistry textbooks on improving students' critical thinking skills on reaction rate material. The research was conducted at MAS Al-Washliyah 26 Tinokkah in the even semester of the 2025/2026 academic year. The sample consisted of 20 students from class XI MIPA 2 as the experimental class and 20 students from class XI MIPA 1 as the control class selected using purposive sampling technique. The research design used was pretest-posttest control group design. The research instruments consisted of a critical thinking skills essay test (5 questions/25 items) that had been validated (r count = 0.901) and a student response questionnaire. The results showed that there was a significant effect of implementing problem-based chemistry textbooks on students' critical thinking skills with a Sig. (2-tailed) value = 0.001 (p < 0.05). The improvement in critical thinking skills in the experimental class was in the high category (N-Gain = 0.87), while the control class was in the medium category (N-Gain = 0.65). Student responses to learning using problem-based textbooks showed positive categories with an average of 96.6% on the understanding indicator and 94.28% on the interest indicator. Thus, the implementation of problem-based high school chemistry textbooks is effective in improving students' critical thinking skills on reaction rate material.